2015
DOI: 10.1071/an13534
|View full text |Cite
|
Sign up to set email alerts
|

A new simple method for estimating the pork carcass mass of primal cuts and lean meat content of the carcass

Abstract: The aim of this study was to develop regression equations for estimating lean meat content and the mass of primal cuts (ham, loin, shoulder, belly) based on selected linear measurements. The experiment involved a classification of 141 pigs from the Polish commercial pig population, with hot carcass weight ranging between 60 and 120 kg. The study population was characterised by high variability in terms of analysed measurements. Eight measurements were made including: mass of half-carcass, backfat thickness at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…Head-on hot carcass weight, fat depth, and muscle depth were similar to values reported in recent studies conducted in Canada ( Miar et al, 2014 ; Zhang et al, 2016 ). Likewise, hot carcass weight (compared between head-on hot carcass weight and head-off hot carcass weight), fat depth, and muscle depth were similar in value with the values reported in recent studies conducted in Europe ( Lisiak et al, 2015 ; Knecht et al, 2016 ) and the United States ( Wilson et al, 2016 ; Arkfeld et al, 2017 ). For example, Wilson et al (2016) reported population statistics for 1,235 commercial pigs in the United States as: 103.6 kg for head-off hot carcass weight, 22 mm for fat depth, and 67 mm for muscle depth.…”
Section: Resultssupporting
confidence: 83%
“…Head-on hot carcass weight, fat depth, and muscle depth were similar to values reported in recent studies conducted in Canada ( Miar et al, 2014 ; Zhang et al, 2016 ). Likewise, hot carcass weight (compared between head-on hot carcass weight and head-off hot carcass weight), fat depth, and muscle depth were similar in value with the values reported in recent studies conducted in Europe ( Lisiak et al, 2015 ; Knecht et al, 2016 ) and the United States ( Wilson et al, 2016 ; Arkfeld et al, 2017 ). For example, Wilson et al (2016) reported population statistics for 1,235 commercial pigs in the United States as: 103.6 kg for head-off hot carcass weight, 22 mm for fat depth, and 67 mm for muscle depth.…”
Section: Resultssupporting
confidence: 83%
“…Lisiak et al [ 17 ] reported, that the regression coefficients for prediction of weight of untrimmed primal cuts (ham, loin, shoulder, belly) were 0.92, 0.87, 0.87, and 0.74, respectively using the Capteur Gras/Maigre (CGM, SYDEL, Lorient, France) equipment in polish commercial pigs.…”
Section: Discussionmentioning
confidence: 99%
“…The LMC of carcasses estimated by devices with one or two measurements does not give much information about primal cuts. Our earlier study (Lisiak et al 2015) presented the fact that for the best prediction of mass of primal cuts, different measurements are necessary. This would lead to a more accurate determination than only LMC of the individual cuts.…”
Section: Discussionmentioning
confidence: 99%
“…Only the automatic AutoFom device, which records a fullbody ultrasound scan, allows for the highly accurate determination of the musculature of all cuts. Accordingly, the demands of the contemporary pork market force increasingly accurate classification and segregation of raw product (Brorsen et al 1998;Lisiak et al 2015;McGlone 2013).…”
Section: Introductionmentioning
confidence: 99%